Activation of Anthocyanin Biosynthesis in Gerbera hybrida (Asteraceae) Suggests Conserved Protein-Protein and Protein-Promoter Interactions between the Anciently Diverged Monocots and Eudicots - Elomaa, Paula (The American Society for Plant Biologists, 2003)
We have identified an R2R3-type MYB factor, GMYB10, from Gerbera hybrida (Asteraceae) that shares high sequence homology to and is phylogenetically grouped together with the previously characterized regulators of anthocyanin pigmentation in petunia (Petunia hybrida) and Arabidopsis. GMYB10 is able to induce anthocyanin pigmentation in transgenic tobacco (Nicotiana tabacum), especially in vegetative parts and anthers. In G. hybrida, GMYB10 is involved in activation of anthocyanin biosynthesis in leaves, floral stems, and flowers. In flowers, its expression is restricted to petal epidermal cell layers in correlation with the anthocyanin accumulation pattern. We have shown, using yeast (Saccharomyces cerevisiae) two-hybrid assay, that GMYB10 interacts with the previously isolated bHLH factor GMYC1. Particle bombardment analysis was used to show that GMYB10 is required for activation of a late anthocyanin biosynthetic gene promoter, PGDFR2. cis-Analysis of the target PGDFR2 revealed a sequence element with a key role in activation by GMYB10/GMYC1. This element shares high homology with the anthocyanin regulatory elements characterized in maize (Zea mays) anthocyanin promoters, suggesting that the regulatory mechanisms involved in activation of anthocyanin biosynthesis have been conserved for over 125 million years not only at the level of transcriptional regulators but also at the level of the biosynthetic gene promoters.